1988
DOI: 10.1111/j.1749-6632.1988.tb31889.x
|View full text |Cite
|
Sign up to set email alerts
|

Erythema Migrans Borreliosis: An HLA‐associated Disease?

Abstract: Erythema migrans borreliosis is a complex multisystemic infectious disorder caused by the spirochetal species termed Borrelia burgdorferi. The clinical picture is characterized by affection of various organ systems such as skin, central and peripheral nervous system, heart, joints, and some other organs. Reports on HLA association to Borrelia burgdorferi infection (BBI) are still controversial. HLA-DR2 was found to be correlated to more severe and/or chronic courses of this infectious disorder.'** However, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
1998
1998

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Steere 23 reported that patients with neuroborreliosis or Lyme arthritis had a significantly increased frequency of HLA-DR4 or DR2, although this was not confirmed by others. 24 Pfluger et al 25 reported that the haplotype combination HLA-A2 and HLA-Cw3 is more frequent in patients with EM. The present patient with facial nerve palsy presented with HLA-DR4, but not HLA-A2 or Cw3.…”
Section: Discussionmentioning
confidence: 99%
“…Steere 23 reported that patients with neuroborreliosis or Lyme arthritis had a significantly increased frequency of HLA-DR4 or DR2, although this was not confirmed by others. 24 Pfluger et al 25 reported that the haplotype combination HLA-A2 and HLA-Cw3 is more frequent in patients with EM. The present patient with facial nerve palsy presented with HLA-DR4, but not HLA-A2 or Cw3.…”
Section: Discussionmentioning
confidence: 99%